Exploring D-Phenylalanine As A Gastro-Protective Chemical Delivery System For Aceclofenac - SUNEELA DHANESHWAR; R. BUCHADE; A. SUTAR; H. KARANDIKAR; K. TEWARI (International Journal of Pharma and Bio Sciences, 2011)
Aceclofenac is a nonsteroidal anti-inflammatory drug used to relieve inflammation and associated pain in various forms of arthritis and has become popular due to its stimulatory effects on cartilage matrix synthesis even though it is known to induce erosion and ulcers in the gastro-intestinal tract. In the present work we synthesized a mutual prodrug of aceclofenac by exploring D-phenylalanine as a gastro-protective carrier system to lower the ulcerogenic potential and enhance effectiveness of aceclofenac as anti-arthritic agent. The study showed that D-phenylalanine enhanced the overall pharmacological and ulcerogenic profile of aceclofenac thus proving its utility as an effective gastro-sparing chemical delivery system in mutual prodrug design.